Safety evaluation of polysaccharides isolated from the water extract of Argemone mexicana L. (Papaveraceae) in Drosophila melanogaster - Adama Denou&&, Abubakar Ahmed&, Dalen Gwatau Dafam, Sunshine Ogwu Ochala, Simeon Omale, Kari Tvete Inngjerdingen, Rokia Sanogo, Drissa Diallo, Berit Smestad Paulsen, John C. Aguiyi (Journal of Applied Pharmaceutical Science, 2020)
Recently, the plant polysaccharides have attracted attention due to their important bioactivities. The literature has shown several pharmacological activities of Argemone mexicana extracts and its components but very few data on its polysaccharides. The current study aimed to evaluate the safety of polysaccharides from A. mexicana. Five polysaccharides [High molecular weight (polysaccharide fraction) of the water extract from Argemone mexicana 1 ( HMAm1), HMAm2, HMAm3, HMAmA1, and HMAmA2] were fractionated from A. mexicana aerial parts by using accelerated solvent extractor procedure followed by ion exchange chromatography of the water decoction extract. The safety assay was carried out using Drosophila melanogaster exposed to the polysaccharides at 12.5 and 25 μg/ ml for 72 hours against a negative control (1% DMSO). After the exposure period, the survival rate and the locomotor capacity of flies were determined. At the end of 72 hours of treatment, all polysaccharide fractions at both doses presented a survival percent of more than 94%. In addition, these polysaccharide fractions affected very little the locomotor performance of the flies. At both doses, HMAm2 presented the highest safety for the flies, while HMAm3 was the least. These findings revealed that polysaccharides from A. mexicana are nontoxic.
Keywords: Polysaccharides, safety, Argemone mexicana, aerial parts, Drosophila melanogaster.